Globalization: a study of domestic firms readiness in industrialising countries / Abd Halim Mohd Noor and Mohamad Saladin Abd Rasool - Mohd Noor, Abd Halim; Abd Rasool, Mohamad Saladin (2002)
It's a forgone conclusion, that the continued existence of firms today largely is influenced by the ability to compete globally. Multinational corporations (MNCs) based in developed countries has longed profited from their ability to compete globally. Despite the seemingly lopsided advantages to MNCs in globalization, local firms in industrializing host countries are also able to reap the benefits if they are ready or prepared for globalization. This paper studies the 'readiness' of local firms in facing globalization. Specifically, this initial study looked at local firms operating in the Malacca industrial estates. This paper employs an unpublished data set of locally-owned firms in various industries operating in Malacca industrial estates. The list of the firms was drawn from a listing provided by the state's Economic Development Corporations - a development arm of the Malacca state government. The data, among others, covers profile, production, resources, marketing practices, procurement from other firms and exporting behavior.